2015
DOI: 10.1111/1750-3841.13134
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Chilling and Partial Freezing on Rigor Mortis Changes of Bighead Carp (Aristichthys nobilis) Fillets: Cathepsin Activity, Protein Degradation and Microstructure of Myofibrils

Abstract: To investigate the effects of chilling and partial freezing on rigor mortis changes in bighead carp (Aristichthys nobilis), pH, cathepsin B, cathepsin B+L activities, SDS-PAGE of sarcoplasmic and myofibrillar proteins, texture, and changes in microstructure of fillets at 4 °C and -3 °C were determined at 0, 2, 4, 8, 12, 24, 48, and 72 h after slaughter. The results indicated that pH of fillets (6.50 to 6.80) was appropriate for cathepsin function during the rigor mortis. For fillets that were chilled and parti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 46 publications
(21 citation statements)
references
References 37 publications
(47 reference statements)
1
19
0
Order By: Relevance
“…In the present study, the textural analysis results could be explained by the dissolution of collagen, because the change in the content of soluble collagen coincides with the decline of hardness and chewiness. Similarly, Lu et al [22] reported the hardness and springiness of bighead carp fillets at 4°C increased until 8 h, followed by a slow decrease to the end of storage.…”
Section: Discussionmentioning
confidence: 75%
“…In the present study, the textural analysis results could be explained by the dissolution of collagen, because the change in the content of soluble collagen coincides with the decline of hardness and chewiness. Similarly, Lu et al [22] reported the hardness and springiness of bighead carp fillets at 4°C increased until 8 h, followed by a slow decrease to the end of storage.…”
Section: Discussionmentioning
confidence: 75%
“…, the reduction in the fillet firmness mainly occurred during the first 3 days of storage and the value decreased to 76%, respect to the initial value. The marked decrease in firmness was in agreement with the results reported in previous study (Liu et al ., ) and might be probably related to the loss of water from the muscle (Wojtysiak & Połtowicz, ) or the reduction in integrity of the muscle cell (Lu et al ., ). Additionally, the activity of endogenous proteases and the rate and extent of energy metabolism as well as the low ultimate pH further affected the texture of fillet (Duun & Rustad, ).…”
Section: Resultsmentioning
confidence: 97%
“…1). Previous studies showed the marked decrease in the firmness and texture of fish fillets during storage (Liu et al, 2013;Zang et al, 2017), which might be related to a reduction in the integrity of muscle cells (Lu et al, 2015). Moreover, it was reported that the extent and rate of energy metabolism, protein degradation, and the activity of endogenous proteases affected the texture of fish fillets (Duun and Rustad, 2008;Zang et al, 2017).…”
Section: Discussionmentioning
confidence: 97%